Basal cell carcinoma in a 14-year-old: A rare case of a common skin cancer - Wahyudi, Danang Tri; Parrol, Firman; Hoemardani, Aida Sofiati; Sutarjo, Agassi Suseno (UI Scholars Hub, 2021)
Background: Basal cell carcinoma (BCC) is the most common cutaneous malignancy. It usually arises in sun-exposed areas of the body, with the face and neck being the most common sites for BCC. BCC is typically found in older individuals, but it is becoming more prevalent in people younger than 50. However, such cases in children under 15 are rarely encountered. Pigmented BCC is a common presentation in people of color, while such presentation is relatively unusual in Caucasians. Pediatric cases could be idiopathic, but it is more commonly associated with a genetic defect, such as basal cell nevus syndrome, xeroderma pigmentosum, Bazex syndrome, and albinism. Those cases could also arise from a congenital lesion, e.g., nevus sebaceous, radiotherapy-related, or solid organ transplant. Case Illustration: We present the case of a 14-year-old boy with a chief complaint of growing tumor on the left cheek since he was 8 years old. He was diagnosed with childhood-onset BCC based on the findings of dermoscopy and skin biopsy. The patient underwent surgical excision of the lesion with 3 mm margins and a full-thickness skin graft obtained from the left retroauricular area. Discussion: Removal of the tumor with clear margins remains the gold standard for BCC treatment. This case presentation showed the best practice for BCC cases in the childhood population. Conclusion: The diagnosis of BCC should not be neglected in the childhood population.